DIGITAL TOOTH COLOR MODELING BEFORE AND AFTER WHITENING: CLINICAL CAPABILITIES AND LIMITATIONS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Predicting and monitoring changes in tooth color during whitening procedures remains a significant challenge in contemporary dentistry. Visual shade assessment methods are often limited by subjective perception, lighting conditions, and individual clinician variability. Digital tooth color modeling technologies offer a more precise and objective measurement, enabling clinicians to anticipate whitening outcomes, enhance treatment planning, and improve patient understanding and satisfaction. However, the accuracy and reliability of these methods depend on the type of discoloration, enamel structure, and software capabilities, necessitating a comprehensive evaluation of their clinical potential and limitations.